HISTÓRIA, TRABALHO E EDUCAÇÃO: ENSINO PROFISSIONALIZANTE DO SENAI PONTA GROSSA, PR - Campones, Kelly Cristina (2012)
The present work of research entitled History, Work and Education: Vocational education at the Senai Ponta Grossa, PR, was developed in the State University of Ponta Grossa in the program of Post-Graduation in Education - Stricto Sensu, in the research line of History and Educational Policies. The research had as general objective to investigate and to analyze the relations of the work with the vocational education of Senai, as well as to analyze the historical mediation inserted in this context. The specific objectives of the research were, to analyze the transformations of the educational processes and professional qualification instituted in important historical phases for consolidation of such modality of education. By means of the inquiry of production organization forms of the professional knowledge, it was possible to describe and to analyze historically the Senai`s consolidation phase in Ponta Grossa, PR. To initiate the research the survey of primary sources was done; subsequently the elaboration research of the state of knowledge, referring to the professional education, additionally, reading and articulation of bibliography which had already been produced on the subject, amongst which I detach: Cunha (1983); (1979); (2000); Kuenzer (1997); Ianni (1988); Senai (1995);Trevisan (1995) and the doctorate theses of Nascimento (2009); Muller (2009) The research presents the historical trajectory of Senai`s institutionalization in Brazil, Curitiba and the city of Ponta Grossa, PR, presenting the existing relations of mediation in the categories of analysis among state, education and work. The challenge of the research was to understand the historical relations for institutionalization of the Senai, in the city of Ponta Grossa, from a general understanding of its institutionalization in Brazil, later in the capital of the Paraná and finally in the related city. It was used to structuralize the research as methodological principle, the historical materialism, which considers the inquiry of the object searched from the reality and in the search to overcome the idealistic conceptions of history. This research was divided in three parts. Firstly, “The work and the professional education in Brazil”, secondly “the relations of the work and the professional education in the State of the Paraná” and the last “Economic relations, political and educational in the consolidation of the Senai in Ponta Grossa,PR”. From this is concluded that, the research contributed for the understanding and agreement of the intentions in the creation of the Senai in the Brazilian territory, which goal, in practical and objective way was to qualify professionals to fit the industrialist`s interests and unlike what the existing speeches in documents and reports, that happened in accordance with a specific social class and also related to political ideologies of the State.